EFFECT OF DIFFERENT NITROGEN SOURCES ON RADIAL GROWTH AND DRY MYCELIAL WEIGHT OF PLEUROTUS DJAMOR (FR.) BOEDIJN - SHARMA, BHARAT BHOOSHAN (Annals of Agricultural Research, 2014)
The research work was carried out at the Mushroom Research Laboratory, Department of Plant Pathology, Indira Gandhi Agricultural University, Raipur. The pure culture of Pleurotus djamor, was procured from Department of Microbiology, Rajendra Agricultural University, Samastipur, Bihar. The results of the investigation indicate that among the different nitrogen sources tested none could promote the growth of P. djamor on solid media. Among the nitrogen sources tested ammonium sulphate, urea, L-asparagine and potassium nitrate were at par with unsupplemented control.